Mahalnya Pembiayaan di Bank Syariah - Sujian Suretno; Rivai Yusuf (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2021)
This study provides a comprehensive picture of the public's perception of the high cost of financing Islamic banks in Indonesia. The perception of "expensive" arises from various perspectives based on the limited knowledge of each customer. In this study, the authors present explanations sourced from Islamic banks and several observers of Islamic banks in Indonesia. Primary data was obtained by conducting in-depth interviews with several Islamic bank practitioners, observations, and documentation studies. The data analysis technique uses the theory of Miles and Huberman, starting from data classification, data reduction, and drawing conclusions. The results of the study found several arguments which then formed the public perception that financing in Islamic banks was considered expensive. The word "expensive" here of course must be understood by defining the correct, authentic meaning, not with a misleading logical approach.